Zuo Lian: Making the Right Kind of “Face” in Online Interactive Classrooms - Hai-Jew, Shalin (My University, 2010)
A research study of 630 Washington Online Virtual Campus learners and the role of trust in high-interactive instructor-led college courses surfaced the importance of instructor and learner telepresence. Particular ways of portraying the self in online space enhanced learning. This paper addresses the research findings on how to make the right kind of face (zuo lian, a colloquial Chinese term on making a social “face” for others) to build more robust trust in interactive online learning.
Keywords: Instructor telepresence; Student telepresence; Distance learning administrator; Trust construct; Virtual communication; Communicating self